Full outline of unresponsiveness score as a predictor of outcomes in critically ill pediatric patients - Novita Purnamasari Assa; Dyah Kanya Wati; Ida Bagus Subanada; Soetjiningsih Soetjiningsih; Made Kardana; Made Sukmawati (Paediatrica Indonesiana, 2020)
Background Mortality predictions are very important for improving service quality in the pediatric intensive care unit (PICU). The full outline of unresponsiveness (FOUR) is a new coma scale and is considered capable of predicting mortality and outcome. Objective To assess the ability of FOUR scores to predict outcomes of critically ill patients in the PICU. Methods This prospective cohort study included children aged 1 months - 18 years who were admitted to the PICU. Subjects were assessed by FOUR, grouped into score < 9 or score >9, and followed until outcomes were obtained. Bivariate analysis to assess the risk of death was made by cross-tabulation and the strength of the association in the form of risk ratio by Chi-square test. Multivariate analysis was done by logistic regression test. Results Of 94 subjects, 47 had FOUR scores <=9 and 47 subjects had FOUR >9. Bivariate analysis revealed that PICU patients with FOUR score <=9 had a higher risk of death than those with FOUR score >9 (RR 12.5; 95%CI 3.1 to 49.8; P<0.0001). Multivariate analysis revealed that FOUR score, length of stay <=7 days, and non-surgical disease significantly increased the risk of mortality in PICU patients (by 42.8 times, 8.9 times, and 5.9 times, respectively). Conclusion The FOUR scores have good ability to predict the outcomes of critically ill pediatric patients. A FOUR score <=9 at the beginning of treatment is significantly associated with the outcome of mortality during treatment in the PICU.